PARADIGMA REFORMASI PENDIDIKAN KONTEMPORER MELALUI PENDEKATAN CLASS ACTION RESEARCH (PENELITIAN TINDAKAN KELAS) - Annas Nur Istiqomah; Dian Hidayati (Jurnal Administrasi Pendidikan, 2023)
This study aims to reveal how the Muhammadiyah Vocational School teachers understand, respond to and implement Classroom Action Research (CAR) to improve the quality of learning practices in the context of contemporary education reform. This research is a qualitative research by making observations through a questionnaire. Research respondents were 60 teachers of SMK Muhammadiyah in Bantul, Yogyakarta, Indonesia. Data were collected through a questionnaire and analyzed to draw conclusions. The results showed that 96.7% percent had not implemented CAR and only 3.3% of teachers had implemented CAR. Barriers to not implementing CAR include factors due to cost and time as well as the ability of teachers. The findings of this study are very important for teacher professional development programs by both government and schools because increasing teacher professionalism will have an impact on student achievement.